2015
DOI: 10.5204/ijcjsd.v4i4.242
|View full text |Cite
|
Sign up to set email alerts
|

Can Collaboration Provide Integrated Services for Prisoners in Norway?

Abstract: In this article, my contention is that Norway's criminal justice policy is increasingly based on principles taken from positive criminology. This means that the correctional service places strong emphasis on establishing collaboration with the local authorities (the municipalities) in order to offer convicted persons integrated services, both during and after serving their sentences. I also point out that positive criminology's principle of viewing convicted persons as unique individuals with individual proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 17 publications
1
15
0
1
Order By: Relevance
“…The participants described the multifaceted needs of offenders, the support needed from a variety of welfare professions and agencies, and the importance of different professions and agencies collaborating to provide the necessary quality of welfare service during this vulnerable transition phase (Theme 1). These views are supported by other Norwegian studies (Friestad & Kjeldberg, 2009;Hansen, 2015;Larsen et al, 2019). Larsen et al (2019) found in their small-scale study that offenders' experiences of support from the welfare services during vulnerable periods, such as reintegration after prison, varied, both within and between services.…”
Section: The Offender's Dependence On Interprofessional and Interagency Collaboration In Reintegration After Prisonsupporting
confidence: 55%
See 2 more Smart Citations
“…The participants described the multifaceted needs of offenders, the support needed from a variety of welfare professions and agencies, and the importance of different professions and agencies collaborating to provide the necessary quality of welfare service during this vulnerable transition phase (Theme 1). These views are supported by other Norwegian studies (Friestad & Kjeldberg, 2009;Hansen, 2015;Larsen et al, 2019). Larsen et al (2019) found in their small-scale study that offenders' experiences of support from the welfare services during vulnerable periods, such as reintegration after prison, varied, both within and between services.…”
Section: The Offender's Dependence On Interprofessional and Interagency Collaboration In Reintegration After Prisonsupporting
confidence: 55%
“…Another Norwegian study, by Friestad and Kjeldberg (2009), found that health promotion among offenders in prison is clearly a multidisciplinary task which requires close collaboration between different welfare service providers and systems of care. Hansen (2015) also highlighted the importance of collaboration, but found that collaboration had proven difficult to establish. He suggested that an explanation is that both the correctional service and the municipalities appear to view problems concerning offenders with substance abuse issues as problems that can be solved separately and sequentially.…”
Section: The Offender's Dependence On Interprofessional and Interagency Collaboration In Reintegration After Prisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen empirical studies were included (see Appendix A). Eight of these had quantitative designs (Bond and Gittell 2010;Fletcher et al 2009;Friestad and Kjelsberg 2009;Hean, Ødegård and Willumsen 2017;Lehman et al 2009;Orrick et al 2011;Shavit et al 2017;Wooditch, Sloas and Taxman 2017) and 11 had qualitative designs (Denton 2014;Friedmann et al 2012;Gunnison and Helfgott 2017;Hannaa et al 2020;Hansen 2015;Hean, Willumsen and Ødegård 2017a;Hean, Willumsen and Ødegård 2017b;Kras 2012;Moore and Hamilton 2016;Samele et al 2016;Yamatani and Spjeldnes 2011). The samples originated in Norway (Friestad and Kjelsberg 2009;Hansen 2015;Hean, Ødegård and Willumsen 2017;Ødegård 2017a, 2017b), the USA (Bond and Gittell 2010;Fletcher et al 2009;Friedmann et al 2012;Gunnison and Helfgott 2017;Hannaa et al 2020;Kras 2012;Lehman et al 2009;Orrick et al 2011;Shavit et al 2017;Wooditch, Sloas and Taxman 2017;Yamatani and Spjeldnes 2011), Australia (Denton 2014), and the UK (Moore and Hamilton 2016;Samele et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…All 19 included studies highlighted the importance of collaboration in meeting the welfare needs of prisoners when they are released from prison (Bond and Gittell 2010;Denton 2014;Fletcher et al 2009;Friedmann et al 2012;Friestad and Kjelsberg 2009;Gunnison and Helfgott 2017;Hannaa et al 2020;Hansen 2015;Hean, Ødegård and Willumsen 2017;Ødegård 2017a, 2017b;Kras 2012;Lehman et al 2009;Moore and Hamilton 2016;Orrick et al 2011;Samele et al 2016;Shavit et al 2017;Wooditch, Sloas and Taxman 2017;Yamatani and Spjeldnes 2011). Denton (2014) concluded that providing services from the mental health department alone was highly insufficient in meeting the complex needs of the targeted group and identified a need for integrated support and treatment during the transition phase from prison to community.…”
Section: Interprofessional Collaboration Is a Prerequisite To Meet Complex Welfare Needsmentioning
confidence: 99%